Maternal Bereavement from an Existential Phenomenological Perspective (REMUNOM, 2024)
The article presents a review of a phenomenological-existential analysis of maternal bereavement. Articles were researched, without a time frame, in the LILACS, BVS and Scielo databases. The topics covered within the theme of maternal bereavement were discussed: existential phenomenology, death, terminal illnesses in children, the mother-child relationship, the relationship between parents after the death of a child and maternal mourning. It was found that bereavement occurs in a subjective way for each person due to various factors, such as the form of the relationship between the deceased and the bereaved. And in the case of terminal illnesses, over time and during hospital visits, anticipatory mourning takes place, i.e., a death that the family knows could happen at any moment. Given that death is a taboo subject in Western society, it is little discussed and addressed, which further hinders its understanding. For this reason, there is a scarcity of studies and articles on the subject, showing the importance of this work.